Various Purification Methods of Seeds of Croton Tiglium Which are Mentioned in Siddha Literature - Nushrath Roshana, M. (Tamilnadu DR.M.G.R. University, India, 2025)
Siddha Toxicology deals with Plants, Metals, Minerals and Animal poison. Croton tiglium is a organic irritant poisonous plant of the family Euohorbiaceae which is the poisonous part seeds used for the treatment of constipation, dyspepsia, dysenteriae, gastrointestinal disorders, intestinal inflammation, rheumatism, peptic ulcer, visceral pain, and headache. Also, it widely used in Siddha system of medicine, specially for purgative action. In the present study, an attempt was made to identify the various purification process of seeds of croton tiglium which are mentioned in the Siddha authentic literacy. Purification is a process which involves the conversion of a substance into beneficial ones. Data were collected from Siddha text books, peer review articles, proceedings, index journals and magazines. There are fifteen methods of purification process found from the above resources. The study illustratesthat, there are 5 (33.33%) simple and 15 (66.66%) complex process of purification. Meanwhile 6(33.33%) animal drug and 12 (66.66%) plant materials are used to purify the seeds of croton tiglium. In these methods, there are 11(60%) short duration methods and 6 (40%) long duration methods respectively. According to the method of purification there are 4(12.90%) soaking, 14 (45.16%)boiling, 4(12.90%) remove the outer covering, 2(6.45%) remove the codlydone, 4 (12.90%) shorting with ghee, 2 (6.45%)pudam method and a(3.22%) thozha method respectively. It is concluded that there are various purification method are found to the seeds of croton tiglium in the various Siddha literatures for the different disease conditions. All the process are have carried out further investigation such as bio chemical analysis, physio chemical analysis, phyto chemical analysis, FTIR analysis, SEM analysis in the future to additive validation in the development of Siddha system of Medicine.
Keywords: Siddha toxicology; Croton tiglium; Purification; Suddhi